Attracting, Preparing, and Retaining Under-Represented Populations in Rural and Remote Alberta-North Communities - Steel, Nancy; Fahy, Patrick J. (International Review of Research in Open and Distributed Learning, 2011)
For several years, the government of the western Canadian province of Alberta has drafted policies and conducted research on the problem of populations under-represented in adult education. This Alberta-North and Athabasca University study, funded by the Alberta government’s Innovation Fund, uses the advice and educational experiences of northern former and present students, and of other community members, to identify ways of better attracting, preparing, and retaining under-represented populations in northern Alberta communities through provision and training in the use of distance delivery methods. The research reported here commences with a review of the literature to investigate the following: 1) the contribution distance education makes globally to learning access in remote areas (and resulting economic growth for under-served populations); 2) how support is provided to retain isolated students; and 3) the help needed to assist remote students to complete distance programs. Community consultations with social service and education agencies in three communities were conducted in order to obtain their perspectives about what helps to attract and support students to educational programs and the barriers students typically encounter, which might be mitigated by distance methods. Finally, a survey was designed and distributed in 87 Alberta-North communities in northern Alberta and across Canada’s Northwest Territories to add perspective to the consultation results.